Asthma, atopy and lung function in young adults after hospitalisation for bronchiolitis in infancy: impact of virus and sex. Issue 1 (19th January 2022) - Sørensen, Karen Galta; Øymar, Knut; Dalen, Ingvild; Halvorsen, Thomas; Mikalsen, Ingvild Bruun
Abstract : Background: Hospitalisation for bronchiolitis is a risk factor for asthma and impaired lung function during childhood, but outcomes in young adults are poorly described. Our primary aim was to study the prevalence of asthma and atopy, and lung function at 17–20 years of age after bronchiolitis in infancy and, secondarily, the impact of viral aetiology (respiratory syncytial virus (RSV) vs non-RSV) and sex on these outcomes. Methods: This Norwegian cohort study enrolled 225 young adults hospitalised for bronchiolitis in infancy during 1996–2001 and 167 matched control subjects. The follow-up included questionnaires for asthma and examinations of lung function and atopy. Outcomes were analysed by mixed effects regressions. Results: Current asthma was more frequent in the postbronchiolitis group versus the control group: 25.1% (95% CI 19.0% to 31.2%) vs 13.1% (95% CI 7.9% to 18.2%), but not atopy: 44.3% (95% CI 37.1% to 51.5%) vs 48.2% (95% CI 40.5% to 55.8%), adjusted predicted proportions (95% CIs). Asthma prevalence did not differ between the RSV group and the non-RSV group: 24.0% (95% CI 16.1% to 32.0%) vs 23.8% (95% CI 12.8% to 34.7%) nor between sexes. Forced expiratory volume in 1 s (FEV1 ), the ratio FEV1 /forced vital capacity (FVC), and forced expiratory flow between 25% and 75% of FVC, were lower in the postbronchiolitis group. Conclusion: Young adults hospitalised for bronchiolitis had higher prevalence of asthma, but not atopy, and a more obstructive lung function pattern than control subjects. The asthma prevalence was high after both RSV bronchiolitis and non-RSV bronchiolitis, and there was no difference between sexes. Bronchiolitis in infancy is associated with respiratory morbidity persisting into young adulthood.